Unveiling the historical function of international criminal courts: between adjudicative and sociopolitical justice - Sander, Barrie (International journal of transitional justice, 2018)
Within the field of international criminal justice, opinion remains divided concerning the extent to which international criminal courts should be expected to write history. Taking this debate as its point of departure, this article argues that contestation over the historical function of international criminal courts hinges on the underlying conception of justice - adjudicative or sociopolitical - to which scholars and practitioners adhere in practice. The article demonstrates how these rival conceptions of justice function less as static positions and more as lines of argumentation that can be deployed to support or critique the range of practices that shape the historical narratives constructed within international criminal courts in practice. The article concludes by identifying a potential avenue to advance the conversation on the historical function - one that would assist in articulating what should legitimately be expected of international criminal courts and enable their practices to be evaluated in a more textured manner.